2007
DOI: 10.1021/bi700330b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure−Activity Relationship Analysis and Molecular Dynamics Simulation To Functionally Validate Nonsynonymous Polymorphisms of Human ABC Transporter ABCB1 (P-Glycoprotein/MDR1)

Abstract: Several preclinical and clinical studies suggest the importance of naturally occurring polymorphisms of drug transporters in the individual difference of drug response. To functionally validate the nonsynonymous polymorphisms of ABCB1 (P-glycoprotein/MDR1) in vitro, we generated SNP variant forms (i.e., S400N, R492C, R669C, I849M, A893P, A893S, A893T, M986V, A999T, P1051A, and G1063A) and expressed them in Sf9 cells. The kinetic properties (Km and Vmax) of those variants were analyzed by measuring the ATPase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 46 publications
1
43
1
4
Order By: Relevance
“…Whereas in the genotype frequencies data, the frequency was observed in patients were CC=15%, CT=59%, and TT=26% and controls were CC=26%, CT=48.5%, TT=25.5% observed, respectively. The silent 3435T>C polymorphism may have some effects on DNA structure, RNA stability, and P-gp function, or it is in linkage disequilibrium with other functional MDR-1 polymorphisms [29]. Our data showed that there was no such significant role of SNP G2677T/C among these study children.…”
Section: Discussionmentioning
confidence: 48%
“…Whereas in the genotype frequencies data, the frequency was observed in patients were CC=15%, CT=59%, and TT=26% and controls were CC=26%, CT=48.5%, TT=25.5% observed, respectively. The silent 3435T>C polymorphism may have some effects on DNA structure, RNA stability, and P-gp function, or it is in linkage disequilibrium with other functional MDR-1 polymorphisms [29]. Our data showed that there was no such significant role of SNP G2677T/C among these study children.…”
Section: Discussionmentioning
confidence: 48%
“…27 CYP3A5 expressors had lower doseadjusted TAC-C 0 concentrations at all studied time points (P # 0.002; Fig. 1; Table 4) and required 2.2-to 2.6-fold higher drug dose to reach the targeted concentration compared with CYP3A5 nonexpressors (Table 4).…”
Section: Associations Of Genetic Variants With Dose-adjusted Drug-c 0mentioning
confidence: 99%
“…The number of viable cells was determined from counts made in a hemocytometer with Trypan blue dye exclusion. Flp-In-293 cells were transfected with the ABCB1-pcDNA5/FRT [26] or ABCG2-pcDNA5/FRT vector [24] (fig. 1a), the Flp recombinase expression plasmid pOG44 and LipofectAmine™-2000 (Invitrogen), as described previously.…”
Section: Methodsmentioning
confidence: 99%